Four new Schizopera (Copepoda, Harpacticoida) from marine interstitial habitats in Korea - Karanovic, Tomislav; Cho, Joo-Lae (Zootaxa, 2016)
With more than 100 valid species, the predominantly marine genus Schizopera Sars, 1905 has a near global distribution. The genus is also relatively successful in invading estuarine and freshwater ecosystems. In Korea only two widely distributed estuarine species have been recorded previously: S. clandestina (Klie, 1924) and S. neglecta Akatova, 1935. Four rare new species discovered in marine interstitial habitats are reported herein. Schizopera daejinensis sp. nov. and S. yeonghaensis sp. nov. are described after a single female and one specimen of each sex respectively. These two species were found living simpatrically in Daejin beach, near Yeong Hae city, on the East Coast of Korea. The minute S. gangneungensis sp. nov. is described after three females from a beach in Gangneung city, also on the East Coast of Korea. Schizopera sindoensis sp. nov. is described after one female and five males from a tiny beach on Jeju Island, on the South Coast of Korea. Our detailed survey of Korean beaches and the absence of any of these species in other localities suggest them to be either short range endemics or anthropogenic relics. We discuss the need for further study and protection of these neglected habitats, and the role they might play in harbouring disproportionate levels of diversity. A variety of phenotypic features for comparative descriptions of the four new species were used, including all cuticular organs (sensilla and pores) on the somites. These minute and underutilized structures provide as much resolution on the species level as traditionally used characters do, with an added bonus of an almost complete lack of sexual dimorphism. This might provide useful directions for future pairing of opposite sexes in these and other copepods, especially in cases of sympatric congeners or missing sexes.